Comparison of bowel dysfunction between colorectal cancer survivors and a non‐operative non‐cancer control group. (3rd February 2020) - Keane, C.; O'Grady, G.; Bissett, I.; Woodfield, J.
Abstract: Aim: Low anterior resection syndrome (LARS) detrimentally affects quality of life in colorectal cancer survivors. This study assessed the prevalence for LARS in colorectal cancer survivors and the same symptoms in a matched control group. Method: Validated instruments, the LARS score and Short Form Survey 12, used to collect functional and quality of life outcomes from patients who had undergone distal colorectal resection at Auckland Hospital (2008–2015) or Dunedin Hospital (2008–2017). A matched non‐operative control group was drawn from patients undergoing surveillance colonoscopy. Results: The response rate was 79%. Cross‐sectional prevalence of major LARS in rectal cancer patients was 52% at a median follow‐up of 52 months. Major LARS prevalence in the sigmoid cancer resection and non‐cancer control groups was similar (25% vs 26%, P  = 0.6). On univariate analysis anastomotic height [risk ratio (RR) for low anterior resection 4.6, P  < 0.001; ultralow anterior resection RR = 15.5, P  < 0.001], radiotherapy (RR = 2.6; P  = 0.009), stoma (RR = 3.6; P  = 0.001) and J pouch reconstruction ( vs straight anastomosis, RR = 4.6; P  = 0.008) were associated with major LARS for rectal cancer patients. These factors were not significant when the analysis was stratified for anastomotic height. Despite correlation between LARS and Short Form Survey 12 outcomes (physical ρ  = −0.2; mental ρ  = −0.2) there was no difference in quality of life outcomes between the groups. Conclusion: Bowel dysfunction after low anterior resection affects the majority of rectal cancer patients. The high background rate of bowel dysfunction must be considered when assessing the prevalence of LARS.